The Tropical Seagrass Halophila stipulacea: Reviewing What We Know From Its Native and Invasive Habitats, Alongside Identifying Knowledge Gaps - Winters, Gidon; Beer, Sven; Willette, Demian A.; Viana, Inés G.; Chiquillo, Kelcie L.; Beca-Carretero, Pedro; Villamayor, Betty; Azcárate-García, Tomás; Shem-Tov, Rachamim; Mwabvu, Bridget; Migliore, Luciana; Rotini, Alice; et al. (Frontiers in Marine Science, 2020)
Halophila stipulacea is a small tropical seagrass, native to the Red Sea, Persian Gulf, and the Indian Ocean. It invaded the Mediterranean Sea 150 years ago as a Lessepsian migrant, but so far has remained in insulated, small populations across this basin. Surprisingly, in 2002 it was reported in the Caribbean Sea, where within a decade it spread to most of the Caribbean Island nations and reaching the South American continent. Unlike its invasion of Mediterranean, in the Caribbean H. stipulacea creates large, continuous populations in many areas. Reports from the Caribbean demonstrated the invasiveness of H. stipulacea by showing that it displaces local Caribbean seagrass species. The motivation for this review comes from the necessity to unify the existing knowledge on several aspects of this species in its native and invasive habitats, identify knowledge gaps and develop a critical strategy to understand its invasive capacity and implement an effective monitoring and conservation plan to mitigate its potential spread outside its native ranges. We systematically reviewed 164 studies related to H. stipulacea to create the “Halophila stipulacea database”. This allowed us to evaluate the current biological, ecological, physiological, biochemical, and molecular knowledge of H. stipulacea in its native and invasive ranges. Here we i) discuss the possible environmental conditions and plant mechanisms involved in its invasiveness, ii) assess the impact of H. stipulacea on native seagrasses and ecosystem functions in the invaded regions, iii) predict the ability of this species to invade European and transoceanic coastal waters, iv) identify knowledge gaps that should be addressed to better understand the biology and ecology of this species both in its native and non-native habitats, which would improve our ability to predict H. stipulacea’s potential to expand into new areas in the future Considering the predicted climate change scenarios and exponential human pressures on coastal areas, we stress the need for coordinated global monitoring and mapping efforts that will record changes in H. stipulacea and its associated communities over time, across its native, invasive and prospective distributional ranges. This will require the involvement of biologists, ecologists, economists, modellers, managers and local stakeholders.